Key tea beverage values driving tourists' memorable experiences: an empirical study in Hong Kong-style cafe memorable experience - Cheung, Man Lai; Leung, Wilson K. S.; Cheah, Jun Hwa; Koay, Kian Yeik; Cheng-Yu Hsu, Bryan (Emerald Publishing, 2021)
Purpose: Using consumption value theory, this study aims to examine the impact of tourists’ perceived consumption value dimensions of tea beverages offered by Hong Kong (HK)-style cafés, including taste value, price value, health value and emotional value, on tourists’ memorable experience (ME), satisfaction and revisit intention. Design/methodology/approach: Using an online survey, this study collected 225 usable data from tourists who had experience in visiting HK-style cafés. Partial least squares–structural equation modelling was used to examine the importance of tourists’ value dimensions, including taste value, price value, health value and emotional value, on tourists’ ME, satisfaction and revisit intention. Findings: The results revealed that taste value, price value, health value and emotional value are significant predictors of tourists’ ME in HK-style cafés, which in turn drive their satisfaction and revisit intention. Research limitations/implications: This study focusses on a single context: HK-style cafés. Future research may enhance the generalisability of the findings by replicating the model in other countries with diverse cultures. Practical implications; Tourism marketers may strengthen tourists’ ME, satisfaction and revisit intention by promoting tea beverages as well as HK-style cafés. Tourism marketers are recommended to communicate taste value, price value, health value and emotional value of HK-style tea beverages, which in turn encourages tourists to learn about the features of tea beverages. Subsequently, it drives tourists’ ME and satisfaction, thereby strengthening their intention to revisit. Originality/value: This study contributes to the tourism marketing literature by providing an understanding of the role of tea beverage value in driving tourists’ ME, satisfaction and revisit intention. By empirically testing a research model, this study confirms that specific consumption value elements of tea beverages, namely, taste value, price value, health value and emotional value, are critical drivers in driving tourists’ ME, satisfaction and revisit intention.